Tantangan Eksistensi Manusia di Era Inovasi Metaverse melalui Eksistensialisme Martin Heidegger - Devika Aenulguri; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
The aim of this research is to answer the challenges of human existence in the metaverse innovation age through Martin Heidegger's existentialism. The method used in this research is a type of qualitative research through literature study. The results of this study, according to Heidegger, the essence of technology is a way of revealing reality. The essence of technique is found in the ontological revolution that occurred in the modern era. The Metaverse creates even more sinister opportunities by shifting human existence in this era. According to Heidegger, humans are not self-creation and even an abandoned existence, but humans must be responsible for their existence. Humans must understand the possibilities. What we call